The effect of exercises on left ventricular systolic and diastolic heart function in sedentary women: Step-aerobic vs core exercises - Guner Cicek; Osman Imamoglu; Abdullah Gullu; Oguzhan Celik; Oguzhan Ozcan; Esin Gullu; Faruk Yamaner (Elsevier, 2017)
The purpose of this study is to investigate the effect of 16 weeks step-aerobic exercises and core exercises on left ventricular structure and function with some physiological parameters in sedentary women. Methods: To achieve the purpose of this study, a total of 45 volunteers including (step-aerobic group (SAG, n = 25), core exercise group (CEG, n = 20) were selected as participants. Two different exercises were applied for 4 days a week, throughout 16 weeks, within 60 minutes for each exercise with the intensity of heart rate (HR) 60-70 percent. The HR was measured using a heart rate monitor for each subject. The physical, biochemical and echocardiographic characteristics of the women were measured before and after the exercise. Results: During the exercise periods, there were a meaningful decrease in the body weight, BMI, value of waist region and hip circumference of the women in both intervention groups as well as in the values of HR, DBP, SBP (p < 0,05). In addition, serum homocysteine (Hcy) and high-sensitivity C-reactive protein (Hs-CRP) levels decreased and the VO2max and left ventricular diastolic end-diastolic dimension increased in both SAG and CEG (p < 0.05). The left ventricular diastolic functions of the SAG improved more than CEG. Left ventricular systolic ejection time and fractional shortening meaningfully improved in both SAG and CEG (p < 0.01). Conclusion: 16 weeks of step-aerobic and core exercise showed significant changes of inflammatory and lipid markers with cardiac dimensions and had favorable effects on both left ventricular systolic function. Left ventricular diastolic function had more improved in SAG than the CEG.